2011
DOI: 10.1111/j.1600-0404.2011.01503.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of Guillain-Barré syndrome in a tropical country: a Brazilian experience

Abstract: A predominance of the AIDP variant was seen, and the incidence of the disease decreased with age. As expected, the distribution of weakness correlated with the clinical variants, and individuals with the axonal variant had a poorer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 38 publications
6
30
1
3
Order By: Relevance
“…As it has been previously reported in other South American countries [47][48][49], the most frequent subphenotype reported in Colombia was AIDP. Conversely, in Mexico AMAN subphenotype is the most frequently observed [50].…”
Section: Discussionsupporting
confidence: 55%
“…As it has been previously reported in other South American countries [47][48][49], the most frequent subphenotype reported in Colombia was AIDP. Conversely, in Mexico AMAN subphenotype is the most frequently observed [50].…”
Section: Discussionsupporting
confidence: 55%
“…3 Tropical pathogens such as flaviviruses are potentially able to affect the nervous system, but most of these neurological manifestations are encephalitic. 4 Only a few sporadic cases of GBS have been reported secondary to dengue virus (DENV) infection, 5,6 West Nile virus (WNV) infection, 7 and Japanese encephalitis virus (JEV) outbreaks. 8 …”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that AMAN is more common in Japan, China, and some countries in Central and South America . In contrast, studies conducted in Brazil and Chile reported a higher prevalence of AIDP in adults . This difference may be related to genetic variations associated with diverse ancestries in South American countries.…”
Section: Discussionmentioning
confidence: 96%